Kewenangan KPPU Terhadap Persekongkolan Tender - Dewi Oktoviana Ustien (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This journal discusses the criteria used to determine the existence of conspiracies in tenders and KPPU's authority in cases of unfair business competition in tenders. This journal uses a method of doctrinal legal research or commonly called Normative legal research. Normative legal research is a legal research conducted by examining library materials or secondary data, or can also be called library legal research. Tender conspiracies that violate Article 22 of Law Number 5 Year 1999 and regarding the determination of administrative sanctions granted by KPPU are always the most common problems. There are six criteria that can be applied to prove the existence of a conspiracy, but if two of the criteria are fulfilled then this can be said as a conspiracy.